Trends in fertiliser use and efficiency in the Great Barrier Reef catchment area - Stephen E. Lewis; Cassandra S. James; Zoe T. Bainbridge; Aaron M. Davis; Adam Northey; Emma Lawrence; Rebecca Bartley (Journal of Environmental Management, 2026)

Changes in lying behaviour of housed ewes prior to parturition and their association with ewe characteristics, measured using accelerometers - Manod Williams; Chelsea N. Davis; Dewi Llyr Jones; Emma S. Davies; Penelope Vasina; David Cutress; Michael T. Rose; Rhys Aled Jones; Hefin Wyn Williams (Applied Animal Behaviour Science, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

AIS underrepresents vessel traffic in Scotland's Marine Protected Areas - Emily L. Hague; Alice Walters; Anna Moscrop; Emma Steel; Katie Dyke; Lauren Hartny-Mills; Alison Lomax; Juliane Lehmann; Sebastian Olias; Carsten Hilgenfeld; Debbie Cole; Sarah MacDonald-Taylor; et al. (Ocean & Coastal Management, 2026)

Association of Immunogenicity and Drug Exposure and the Importance of Target Engagement in ADA Development: A Clinical Case Study of Anti-SARS-CoV-2 Biotherapeutics - Susan C. Irvin; Samit Ganguly; Zhiqiang Wang; Zhongqing Will He; Marguerite Alejandro; Kaitlin Donohue; Chinnasamy Elango; Chris Gallo; Stephen Guttmann; Shawn Kalicharan; Kristina Kameron; James Laird; et al. (The AAPS Journal, 2025)
The administration of therapeutic proteins, such as monoclonal antibodies (mAbs) may result in the formation of anti-drug antibodies (ADA), but there is limited publicly available data for biotherapeutics with exogenous targets or with targets in low abundance systemically. ADAs can impact a biotherapeutic’s safety, efficacy, and pharmacokinetics, so evaluation of immunogenicity is required for all therapeutic proteins. This analysis sought to evaluate the immunogenicity of two mAbs against COVID-19, casirivimab (CAS) and imdevimab (IMD) administered as a cocktail (CAS + IMD), in multiple clinical trials across different participant populations to add knowledge about the immunogenicity risk of protein therapeutics against exogenous targets and the association between immunogenicity and drug exposure. Overall, the incidence of treatment-boosted and treatment-emergent ADAs and neutralizing antibodies in both disease treatment and prophylaxis settings were low (i.e., < 11%). Participants in these studies were followed for up to 225 days post-last dose. Over time, the incidence of treatment-emergent and treatment-boosted immunogenicity for each mAb increased, but the rates and titers remained low overall; when it developed, patients usually developed ADA to both mAbs. Frequency of administration, dose, and route of administration did not appear to impact rates of immunogenicity. Concentrations of CAS and IMD were similar between participants of different immunogenicity status, indicating immunogenicity of CAS and IMD had no impact on pharmacokinetics of these mAbs; there was also no observed impact on safety or efficacy. The data presented here may provide supportive information for assessing the immunogenicity risk of protein therapeutics with exogenous targets. Graphical Abstract

We are what ‘we’ eat: How do close social relationship dynamics in the household impact the sustainability of diets? - Tess Davis; Sophie Duncan; Rebecca Gregson; Emma Garnett; Jared Piazza; Sharon Simpson; Esther K. Papies (Appetite, 2025)

Marine monitors: Land-based citizen science observations show AIS data underrepresents coastal vessel traffic co-occurring with marine mammals - Emily Hague; Alice Walters; Anna Moscrop; Emma Steel; Katie Dyke; Carole Davis; Bernard Siddle; Debbie Cole; Sarah MacDonald-Taylor; Peter Gulliver; Rebecca Olaleye; Juliane Lehmann; et al. (Biological Conservation, 2025)

AIS data underrepresents vessel traffic around coastal Scotland - Emily Hague; Alice Walters; Anna Moscrop; Emma Steel; Katie Dyke; Lauren Hartny-Mills; Alison Lomax; Rebecca Dudley; Pippa Garrard; Jenny Hampson; Sadie Gorvett; Hannah Lightley; et al. (Marine Policy, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Longitudinal Analysis of Urban Stormwater Microbiome and Resistome from Watersheds with and without Green Infrastructure using Long-Read Sequencing - Molly Mills; Angela Davis; Emma Lancaster; Boseung Choi; Jay Martin; Ryan Winston; Jiyoung Lee (Water Research, 2024)

Contribution of the veterinary profession to the Australian animal health surveillance system and opportunities for future contributions - Marta Hernandez-Jover; Emma Davis; Lynne Hayes; Jennifer Manyweathers; Yiheyis Maru; Robert Woodgate (Preventive Veterinary Medicine, 2024)

Excavating the ‘Rutland Sea Dragon’: The largest ichthyosaur skeleton ever found in the UK (Whitby Mudstone Formation, Toarcian, Lower Jurassic) - Nigel R. Larkin; Dean R. Lomax; Mark Evans; Emma Nicholls; Steven Dey; Ian Boomer; Philip Copestake; Paul Bown; James B. Riding; Darren Withers; Joseph Davis (Proceedings of the Geologists' Association, 2023)

Remote cameras capture dung burial by burrowing cricket - Emma F. Zeitler; Marcus A. Lashley; Ava Blanc; Logan R. Davis; Sarah E. Dill; Olivia H. McGehee; Blair A. McLean; Elijah C. Smith (Food Webs, 2023)

The faunal Ponto-Caspianization of central and western European waterways - Ismael Soto; Ross N. Cuthbert; Anthony Ricciardi; Danish A. Ahmed; Florian Altermatt; Ralf B. Schäfer; Gaït Archambaud-Suard; Núria Bonada; Miguel Cañedo-Argüelles; Zoltán Csabai; Thibault Datry; Jaimie T. A. Dick; et al. (Biological Invasions, 2023)
As alien invasive species are a key driver of biodiversity loss, understanding patterns of rapidly changing global species compositions depends upon knowledge of invasive species population dynamics and trends at large scales. Within this context, the Ponto-Caspian region is among the most notable donor regions for aquatic invasive species in Europe. Using macroinvertebrate time series collected over 52 years (1968–2020) at 265 sites across 11 central and western European countries, we examined the occurrences, invasion rates, and abundances of freshwater Ponto-Caspian fauna. We examined whether: (i) successive Ponto-Caspian invasions follow a consistent pattern of composition pioneered by the same species, and (ii) Ponto-Caspian invasion accelerates subsequent invasion rates. In our dataset, Ponto-Caspian macroinvertebrates increased from two species in 1972 to 29 species in 2012. This trend was parallelled by a non-significant increasing trend in the abundances of Ponto-Caspian taxa. Trends in Ponto-Caspian invader richness increased significantly over time. We found a relatively uniform distribution of Ponto-Caspian macroinvertebrates across Europe without any relation to the distance to their native region. The Ponto-Caspian species that arrived first were often bivalves (46.5% of cases), particularly Dreissena polymorpha , followed secondarily by amphipods (83.8%; primarily Chelicorophium curvispinum and Dikerogammarus villosus ) . The time between consecutive invasions decreased significantly at our coarse regional scale, suggesting that previous alien establishments may facilitate invasions of subsequent taxa. Should alien species continue to translocate from the Ponto-Caspian region, our results suggest a high potential for their future invasion success highly connected central and western European waters. However, each species’ population may decline after an initial ‘boom’ phase or after the arrival of new invasive species, resulting in different alien species dominating over time.

Using camera trap bycatch data to assess habitat use and the influence of human activity on African elephants (Loxodonta africana) in Kasungu National Park, Malawi - Robert S. Davis; Louise K. Gentle; William O. Mgoola; Emma L. Stone; Antonio Uzal; Richard W. Yarnell (Mammalian Biology, 2023)
African elephants ( Loxodonta africana ) are increasingly exposed to high levels of human disturbance and are threatened by poaching and human–elephant conflict. As anthropogenic pressures continue to increase, both inside and outside protected areas, understanding elephant behavioural responses to human activity is required for future conservation management. Here, we use bycatch data from camera trap surveys to provide inferences on elephant habitat use and temporal activity in Kasungu National Park (KNP), Malawi. The KNP elephant population has declined by ~ 95% since the late 1970s, primarily because of intensive poaching, and information on elephant ecology and behaviour can assist in the species’ recovery. Using occupancy modelling, we show that proximity to water is the primary driver of elephant habitat use in KNP, with sites closer to water having a positive effect on elephant site use. Our occupancy results suggest that elephants do not avoid sites of higher human activity, while results from temporal activity models show that elephants avoid peak times of human activity and exhibit primarily nocturnal behaviour when using the KNP road network. As key park infrastructure is located near permanent water sources, elephant spatiotemporal behaviour may represent a trade-off between resource utilisation and anthropogenic-risk factors, with temporal partitioning used to reduce encounter rates. Increased law enforcement activity around permanent water sources could help to protect the KNP elephant population during the dry season. Our findings highlight that camera trap bycatch data can be a useful tool for the conservation management of threatened species beyond the initial scope of research.

Habitat structure and the presence of large carnivores shape the site use of an understudied small carnivore: caracal ecology in a miombo woodland - Robert S. Davis; Louise K. Gentle; William O. Mgoola; Emma L. Stone; Antonio Uzal; Richard W. Yarnell (Mammal Research, 2023)
Basic ecological knowledge on African small carnivores and how they interact with the wider carnivore guild are lacking for many species. The caracal ( Caracal caracal ) has a widespread distribution across Africa, yet there is a paucity of information on this species outside of savannah and agricultural landscapes. Using camera trap data from Kasungu National Park, Malawi, we provide novel information on caracal habitat use in a miombo woodland and compare the spatiotemporal dynamics between caracal and members of the large carnivore guild (leopard, Panthera pardus and spotted hyaena, Crocuta crocuta ). We found that caracal were more likely to use sites with higher grass cover and further away from permanent water sources. Caracal site use increased in areas with lower spotted hyaena abundance and caracal exhibited different temporal activity patterns to spotted hyaena. In contrast, caracal did not exhibit spatial or temporal avoidance of leopard at the scale investigated here. However, the probability of detecting caracal at sites of higher leopard abundance was significantly lower, suggesting possible behavioural mechanisms to avoid interaction. Our study provides an insight into caracal ecology in a miombo woodland and improves our understanding of community dynamics between a lesser-studied small carnivore and the large carnivore guild.

Plant–Environment Interactions in the Low Arctic Torngat Mountains of Labrador - Emma Davis; Andrew Trant; Luise Hermanutz; Robert G. Way; Antoni G. Lewkowicz; Laura Siegwart Collier; Alain Cuerrier; Darroch Whitaker (Ecosystems, 2021)
The eastern Canadian Subarctic and Arctic are experiencing significant environmental change with widespread implications for the people, plants, and animals living there. In this study, we integrate 10 years of research at the Nakvak Brook watershed in Torngat Mountains National Park of Canada, northern Labrador, to assess the sensitivity of ecological and geomorphological systems to regional climate warming. A time series of the Normalized Difference Vegetation Index indicates that the area has undergone a significant greening trend over the past four decades. Analyses of shrub cross sections suggest that greening has been caused by a combination of rapid establishment and growth that began in the late 1990’s and coincided with warmer growing season temperatures. Recent (2010–2015) vegetation change has been subtle and heavily moderated by soil moisture status. Plant canopy height is greater in wet areas and has an insulating effect on ground surface temperatures during the winter, a consequence of snow trapping by shrub canopies. Observations of subsurface conditions indicate that the study site is best characterized as having discontinuous near-surface permafrost. The importance of subsurface conditions for above-ground vegetation depends on the geomorphological context, with plants in wet areas underlain by fine materials being the most likely to be growth-limited by permafrost, thus being potential hot-spots for future change. With the expectation of sustained climate change, loss of adjacent sea ice, and proximity to the forest-tundra ecotone, it is likely that the Torngat Mountains will continue to be an area of rapid environmental change in the coming decades.

Smoke on the Water: Comparative Assessment of Combined Thermal Shock Treatments for Control of Invasive Asian Clam, Corbicula fluminea - Neil E. Coughlan; Ross N. Cuthbert; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Gina Y. W. Vong; Emma Healey; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Jaimie T. A. Dick (Environmental Management, 2021)
Suppression of established populations of invasive alien species can be a complex and expensive process, which is frequently unsuccessful. The Asian clam, Corbicula fluminea (Müller, 1774), is considered a high impact invader that can adversely alter freshwater ecosystems and decrease their socioeconomic value. To date, C. fluminea continues to spread and persist within freshwater environments worldwide, despite repeated management attempts to prevent dispersal and suppress established populations. As extensive C. fluminea beds can often become exposed during low-water conditions, the direct application of hot or cold thermal shock treatments has been proposed as suitable mechanism for their control. Further, mechanical substrate disturbance may enhance the efficacy of thermal shock treatments by facilitating exposures to multiple layers of buried clams. In the present study, we advanced these methods by assessing combined applications of both hot and cold thermal shock treatments for control of C. fluminea , using steam spray (≥100 °C; 350 kPa), low- or high-intensity open-flame burns (~1000 °C) and dry ice (−78 °C). In a direct comparison of raking combined with hot thermal shock applications, both steam and high-intensity open-flame treatments tended to be most effective, especially following multiple applications. In addition, when hot thermal treatments are followed by a final cold shock (i.e. dry ice), steam treatments tended to be most effective. Further, when dry ice was applied either alone or prior to an application of a hot shock treatment, substantial if not complete C. fluminea mortality was observed. Overall, this study demonstrated that combined applications of hot and cold thermal shock treatments, applied following the disruption of the substrate, can substantially increase C. fluminea mortality compared to separate hot or cold treatments.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Grasping at digitalisation: turning imagination into fact in the sugarcane farming community - Simon J. Fielke; Bruce M. Taylor; Emma Jakku; Martijn Mooij; Cara Stitzlein; Aysha Fleming; Peter J. Thorburn; Anthony J. Webster; Aaron Davis; Maria P. Vilas (Sustainability Science, 2021)
Nutrient runoff from catchments that drain into the Great Barrier Reef (GBR) is a significant source of stress for this World Heritage Area. An alliance of collaborative on-ground water quality monitoring (Project 25) and technologically driven digital application development (Digiscape GBR) projects were formulated to provide data that highlighted the contribution of a network of Australian sugar cane farmers, amongst other sources, to nutrient runoff. This environmental data and subsequent information were extended to the farming community through scientist-led feedback sessions and the development of specialised digital technology (1622™WQ) that help build an understanding of the nutrient movements, in this case nitrogen, such that farmers might think about and eventually act to alter their fertilizer application practices. This paper reflects on a socio-environmental sustainability challenge that emerged during this case study, by utilising the nascent concept of digi-grasping. We highlight the importance of the entire agricultural knowledge and advice network being part of an innovation journey to increase the utility of digital agricultural technologies developed to increase overall sustainability. We develop the digi-MAST analytical framework, which explores modes of being and doing in the digital world, ranging from ‘the everyday mystery of the digital world (M)’, through digital ‘awareness (A)’, digitally ‘sparked’ being/s (S), and finally the ability of individuals and/or groups to ‘transform (T)’ utilising digital technologies and human imaginations. Our digi-MAST framework allows us to compare agricultural actors, in this case, to understand present modes of digi-grasping to help determine the resources and actions likely to be required to achieve impact from the development of various forms of digital technological research outputs.

Correction to: Regional variability in the response of alpine treelines to climate change - Emma L. Davis; Robert Brown; Lori Daniels; Trudy Kavanagh; Ze’ev Gedalof (Climatic Change, 2020)

Steam and Flame Applications as Novel Methods of Population Control for Invasive Asian Clam (Corbicula fluminea) and Zebra Mussel (Dreissena polymorpha) - Neil E. Coughlan; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Emma Healey; Jaimie T. A. Dick; Gina Y. W. Vong; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Ross N. Cuthbert (Environmental Management, 2020)
Control strategies for established populations of invasive alien species can be costly and complex endeavours, which are frequently unsuccessful. Therefore, rapid-reaction techniques that are capable of maximising efficacy whilst minimising environmental damage are urgently required. The Asian clam ( Corbicula fluminea Müller, 1774), and the zebra mussel ( Dreissena polymorpha Pallas, 1771), are invaders capable of adversely affecting the functioning and biodiversity of freshwater ecosystems. Despite efforts to implement substantial population-control measures, both species continue to spread and persist within freshwater environments. As bivalve beds often become exposed during low-water conditions, this study examined the efficacy of steam-spray (≥100 °C, 350 kPa) and open-flame burn treatments (~1000 °C) to kill exposed individuals. Direct steam exposure lasting for 5 min caused 100% mortality of C. fluminea buried at a depth of 3 cm. Further, combined rake and thermal shock treatments, whereby the substrate is disturbed between each application of either a steam or open flame, caused 100% mortality of C. fluminea specimens residing within a 4-cm deep substrate patch, following three consecutive treatment applications. However, deeper 8-cm patches and water-saturated substrate reduced maximum bivalve species mortality rates to 77% and 70%, respectively. Finally, 100% of D. polymorpha specimens were killed following exposure to steam and open-flame treatments lasting for 30 s and 5 s, respectively. Overall, our results confirm the efficacy of thermal shock treatments as a potential tool for substantial control of low-water-exposed bivalves. Although promising, our results require validation through upscaling to field application, with consideration of other substrate types, increased substrate depth, greater bivalve densities, non-target and long-term treatment effects.

Regional variability in the response of alpine treelines to climate change - Emma L. Davis; Robert Brown; Lori Daniels; Trudy Kavanagh; Ze’ev Gedalof (Climatic Change, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Characterization and spatial distribution of organic-contaminated sediment derived from historical industrial effluents - Emma Hoffman; Masi Alimohammadi; James Lyons; Emily Davis; Tony R. Walker; Craig B. Lake (Environmental Monitoring and Assessment, 2019)

Internal waves influence the thermal and nutrient environment on a shallow coral reef - Emma C. Reid; Thomas M. DeCarlo; Anne L. Cohen; George T. F. Wong; Steven J. Lentz; Aryan Safaie; Austin Hall; Kristen A. Davis (Limnology and Oceanography, 2019)
Internal waves can influence water properties in coastal ecosystems through the shoreward transport and mixing of subthermocline water into the nearshore region. In June 2014, a field experiment was conducted at Dongsha Atoll in the northern South China Sea to study the impact of internal waves on a coral reef. Instrumentation included a distributed temperature sensing system, which resolved spatially and temporally continuous temperature measurements over a 4‐km cross‐reef section from the lagoon to 50‐m depth on the fore reef. Our observations show that during summer, internal waves shoaling on the shallow atoll regularly transport cold, nutrient‐rich water shoreward, altering near‐surface water properties on the fore reef. This water is transported shoreward of the reef crest by tides, breaking surface waves and wind‐driven flow, where it significantly alters the water temperature and nutrient concentrations on the reef flat. We find that without internal wave forcing on the fore reef, temperatures on the reef flat could be up to 2.0°C ± 0.2°C warmer. Additionally, we estimate a change in degree heating weeks of 0.7°C‐weeks warmer without internal waves, which significantly increases the probability of a more severe bleaching event occurring at Dongsha Atoll. Furthermore, using nutrient samples collected on the fore reef during the study, we estimated that instantaneous onshore nitrate flux is about four‐fold higher with internal waves than without internal waves. This work highlights the importance of internal waves as a physical mechanism shaping the nearshore environment, and likely supporting resilience of the reef.

Flower‐visitor communities of an arcto‐alpine plant—Global patterns in species richness, phylogenetic diversity and ecological functioning - Mikko Tiusanen; Tea Huotari; Paul D. N. Hebert; Tommi Andersson; Ashley Asmus; Joël Bêty; Emma Davis; Jennifer Gale; Bess Hardwick; David Hik; Christian Körner; Richard B. Lanctot; et al. (Molecular Ecology, 2019)
Pollination is an ecosystem function of global importance. Yet, who visits the flower of specific plants, how the composition of these visitors varies in space and time and how such variation translates into pollination services are hard to establish. The use of DNA barcodes allows us to address ecological patterns involving thousands of taxa that are difficult to identify. To clarify the regional variation in the visitor community of a widespread flower resource, we compared the composition of the arthropod community visiting species in the genus Dryas (mountain avens, family Rosaceae), throughout Arctic and high‐alpine areas. At each of 15 sites, we sampled Dryas visitors with 100 sticky flower mimics and identified specimens to Barcode Index Numbers ( BIN s) using a partial sequence of the mitochondrial COI gene. As a measure of ecosystem functioning, we quantified variation in the seed set of Dryas . To test for an association between phylogenetic and functional diversity, we characterized the structure of local visitor communities with both taxonomic and phylogenetic descriptors. In total, we detected 1,360 different BIN s, dominated by Diptera and Hymenoptera. The richness of visitors at each site appeared to be driven by local temperature and precipitation. Phylogeographic structure seemed reflective of geological history and mirrored trans‐Arctic patterns detected in plants. Seed set success varied widely among sites, with little variation attributable to pollinator species richness. This pattern suggests idiosyncratic associations, with function dominated by few and potentially different taxa at each site. Taken together, our findings illustrate the role of post‐glacial history in the assembly of flower‐visitor communities in the Arctic and offer insights for understanding how diversity translates into ecosystem functioning.

Limited prospects for future alpine treeline advance in the Canadian Rocky Mountains - Emma L. Davis; Ze’ev Gedalof (Global Change Biology, 2018)
Treeline advance has occurred throughout the twentieth century in mountainous regions around the world; however, local variation and temporal lags in responses to climate warming indicate that the upper limits of some treelines are not necessarily in climatic equilibrium. These observations suggest that factors other than climate are constraining tree establishment beyond existing treelines. Using a seed addition experiment, we tested the effects of seed availability, predation and microsite limitation on the establishment of two subalpine tree species ( Picea engelmannii and Abies lasiocarpa ) across four treelines in the Canadian Rocky Mountains. The effect of vegetation removal on seedling growth was also determined, and microclimate conditions were monitored. Establishment limitations observed in the field were placed in context with the effects of soil properties observed in a parallel experiment. The seed addition experiment revealed reduced establishment with increasing elevation, suggesting that although establishment within the treeline ecotone is at least partially seed limited, other constraints are more important beyond the current treeline. The effects of herbivory and microsite availability significantly reduced seedling establishment but were less influential beyond the treeline. Microclimate monitoring revealed that establishment was negatively related to growing season temperatures and positively related to the duration of winter snow cover, counter to the conventional expectation that establishment is limited by low temperatures. Overall, it appears that seedling establishment beyond treeline is predominantly constrained by a combination of high soil surface temperatures during the growing season, reduced winter snowpack and unfavourable soil properties. Our study supports the assertion that seedling establishment in alpine treeline ecotones is simultaneously limited by various climatic and nonclimatic drivers. Together, these factors may limit future treeline advance in the Canadian Rocky Mountains and should be considered when assessing the potential for treeline advance in alpine systems elsewhere

Long-term environmental change and shifts in the aquatic plant community of Jones Creek, Thousand Islands National Park, Ontario, Canada based on plant macrofossil analysis - Ryan Boxem; Emma L. Davis; Jesse C. Vermaire (Journal of Paleolimnology, 2018)

Investigating the prostate specific antigen, body mass index and age relationship: is an age–BMI-adjusted PSA model clinically useful? - Sean Harrison; Kate Tilling; Emma L. Turner; J. Athene Lane; Andrew Simpkin; Michael Davis; Jenny Donovan; Freddie C. Hamdy; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2016)

Erratum to: Heritability and genome-wide analyses of problematic peer relationships during childhood and adolescence - Beate St Pourcain; C. M. A. Haworth; O. S. P. Davis; Kai Wang; Nicholas J. Timpson; David M. Evans; John P. Kemp; Angelica Ronald; Tom Price; Emma Meaburn; Susan M. Ring; Jean Golding; et al. (Human Genetics, 2016)

Spatial variability of recent macroscopic charcoal deposition in a small montane lake and implications for reconstruction of watershed-scale fire regimes - Colin J. Courtney Mustaphi; Emma L. Davis; Joelle T. Perreault; Michael F. J. Pisaric (Journal of Paleolimnology, 2015)

Heritability and genome-wide analyses of problematic peer relationships during childhood and adolescence - Beate St Pourcain; C. M. A. Haworth; O. S. P. Davis; Kai Wang; Nicholas J. Timpson; David M. Evans; John P. Kemp; Angelica Ronald; Tom Price; Emma Meaburn; Susan M. Ring; Jean Golding; et al. (Human Genetics, 2015)

Evaluating the suitability of nine shelterbelt species for dendrochronological purposes in the Canadian Prairies - Emma L. Davis; Colin P. Laroque; Ken Van Rees (Agroforestry Systems, 2013)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Paleolimnological investigations of anthropogenic environmental change in Lake Tanganyika: V. Palynological evidence for deforestation and increased erosion - Emma S. Msaky; Daniel Livingstone; Owen K. Davis (Journal of Paleolimnology, 2005)